Community aid and support (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article provides the information about the role of community support and belonging, identity in our lives. This assistance connects an individual to the society and strengthens our ties with people, making it a better place for us to live. As well as this feature assure people with the information, advice, guidance and also tangible support, such as assistance in times of uncertainty